Novel oxazolidinones harbor potent in vitro activity against the clinical isolates of multidrug-resistant Mycobacterium tuberculosis in China - Wang, Chenqian; Wang, Guirong; Huo, Fengmin; Xue, Yi; Jia, Junnan; Dong, Lingling; Zhao, Liping; Wang, Fen; Huang, Hairong; Duan, Hongfei (Frontiers in Medicine, 2022)
Abstract Objective: To investigate the in vitro activities of five oxazolidinones in parallel against the reference strains of different mycobacterial species and clinical isolates of M. tuberculosis (Mtb), and shed light on the differences in the efficacy of these homolog drugs. Methods: The minimum inhibitory concentrations (MICs) of linezolid, tedizolid, sutezolid, delpazolid, and contezolid against 16 mycobacterial reference strains and 69 M. tuberculosis clinical isolates, including 17 drug-susceptible isolates and 52 multidrug-resistant (MDR) isolates, were determined by microplate alamarBlue assay (MABA). The intracellular killing activities of contezolid and linezolid against Mtb H37Rv were compared. In addition, mutations in the linezolid resistance-related genes (rplC, rplD, and 23S rRNA) of the Mtb clinical isolates were also analyzed. Results: Sutezolid exhibited the strongest inhibitory activities against the reference strains of both rapidly-growing mycobacteria (RGM) and slowly-growing mycobacteria (SGM), among the tested oxazolidinones. In contrast, tedizolid only manifested potent activity against reference strains of SGM. Linezolid, delpazolid, and contezolid were less active against the nontuberculous mycobacterial references. For the Mtb clinical isolates, the antimicrobial action was ranked as: sutezolid> tedizolid> contezolid and linezolid> delpazolid, whereas no difference between drug-sensitive and multiple drug-resistant isolates was observed. Notably, contezolid demonstrated obviously superior intracellular antimicrobial activity than linezolid. Few strains harbored mutations in rrl gene or rplD genes, although these strains had drug susceptible profiles to linezolid. Conclusion: Different oxazolidinones can have discrepant antimicrobial activity against different mycobacterial species, or have different manifestations out of cell or in cell. Understanding these differences would be helpful in choosing the appropriate drug in clinical practice.